2022
DOI: 10.3390/jcm11143926
|View full text |Cite
|
Sign up to set email alerts
|

Hip Fractures and Visual Impairment: Is There a Cause–Consequence Mechanism?

Abstract: Background: Numerous studies have pointed out how visual impairment relates to falls in the elderly, causing dangerous consequences, such as fractures. The proximal femur fracture is one of the most frequent fracture types related to poor vision. This study investigates the link between fall-related hip fractures and visual impairment. Methods: The present is an observational monocentric case–control study. We collected the ophthalmologic anamnesis and measured the visual acuity of 88 subjects with femur neck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, most of these studies only assessed a limited aspect of the global visual functioning, that it to say visual acuity. Other studies showed a lack of association between fracture risk and visual impairment when only visual acuity was evaluated ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies only assessed a limited aspect of the global visual functioning, that it to say visual acuity. Other studies showed a lack of association between fracture risk and visual impairment when only visual acuity was evaluated ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…The causal association between uncorrected visual impairment, mental and behavioral changes, and elevated mortality rates is still subject to uncertainty. In fact, there is a dearth of circumstantial data supporting the advantages of using refractive lenses [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%